2018
DOI: 10.1177/0269881117750153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation ofGRIA3gene is associated with vulnerability to methamphetamine dependence and its associated psychosis

Abstract: Methamphetamine (METH) is an addictive psychostimulant drug commonly leading to schizophrenia-like psychotic symptoms. Disturbances in glutamatergic neurotransmission have been proposed as neurobiological mechanisms and the α-amino-3 hydroxy-5 methyl-4 isoxazole propionic acid (AMPA) glutamate receptor has been implicated in these processes. Moreover, genetic variants in GRIAs, genes encoding AMPA receptor subunits, have been observed in association with both drug dependence and psychosis. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
(92 reference statements)
1
5
0
Order By: Relevance
“…Based on the current result regarding to rs3813296, deficit Ca 2+ permeability should be associated with the variation of T to G. However, this variation has significant relevance to the enhanced connection strength of R. dLPFC → R. thalamus, which could be interpreted as compensation phenomenon. A literature study returned two studies containing rs3813296 (Crisafulli et al, 2012;Iamjan et al, 2018). Few studies are similar with our study; thus, we tried to search for supporting results from the current dataset and found that the white matter volume of the superior corona radiata in schizophrenia patients with the GT genotype is significantly larger than those with the TT genotype.…”
Section: Main Effect Of Rs3813296 On Causality Connectivity In the Frsupporting
confidence: 64%
“…Based on the current result regarding to rs3813296, deficit Ca 2+ permeability should be associated with the variation of T to G. However, this variation has significant relevance to the enhanced connection strength of R. dLPFC → R. thalamus, which could be interpreted as compensation phenomenon. A literature study returned two studies containing rs3813296 (Crisafulli et al, 2012;Iamjan et al, 2018). Few studies are similar with our study; thus, we tried to search for supporting results from the current dataset and found that the white matter volume of the superior corona radiata in schizophrenia patients with the GT genotype is significantly larger than those with the TT genotype.…”
Section: Main Effect Of Rs3813296 On Causality Connectivity In the Frsupporting
confidence: 64%
“…The seven selected genes in signature have been studied and reported previously [42][43][44]. For instance, TRIM67, the most evolutionarily conserved member of tripartite motif (TRIM) family, was reported to function as a Ras inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variability in AMPAR genes has been associated with different neurological traits in humans such as sleep pattern [ 10 ], migraine [ 11 , 12 ] and psychoactive drug addiction [ 13 , 14 ]. Currently, pathogenic variants in all the AMPAR genes have been reported in subjects presenting with syndromic intellectual disability.…”
Section: Introductionmentioning
confidence: 99%